Hubungan Insidensi Penyakit Hawar Pelepah dengan Keparahan Penyakit dan Hasil Produksi Padi - Milati, Laila Nur; Nuryanto, Bambang; Sumarlin, Umin (Jurnal Fitopatologi Indonesia, 2021)
The Relationship between Sheath Blight Disease Incidence, Disease Severity, and Rice Yield Sheath blight disease on rice caused by Rhizoctonia solani may interfere crop production. This study aimed to estimate yield loss of rice due to sheath blight disease based on disease severity at harvest period. The experiment was carried out at the screenhouse and experimental field of the Indonesian Center for Rice Research in the 2019/2020 rainy season. Three rice varieties, “Ciherang”, “Inpari 32 HDB”, and “Baroma” were involved in screenhouse experiment; while in the experimental field only involved “Ciherang”. Inoculation of R. solani was done by placing infected plants as source of inoculum in the plants’ rows with disease incidence rate of 5%–50%. Disease severity on the plants in the screenhouse and experimental field continued to increase during the observation period and reached 60.09% and 70.56%, respectively. Furthermore, high disease severity leads to high yield losses. Knowledge of the relationship between disease incidence and severity is useful to predict yield losses so that disease control can be carried out as early as possible to avoid high yield losses.